FRI0153 Cardiovascular autonomic functions and sympathetic skin responses in behÇet's disease. (1st June 2001) - Aksu, K; Colakoglu, Z; Keser, G; Kýylýoglu, N; Inal, V; Gumusdýs, G; Doganavsargýl, E
Abstract : Background: Unlike other systemic necrotizing vasculitides, such as periarteritis nodosa and Churg-Strauss Syndrome, peripheral and autonomic nervous system involvement is rare Behçet's disease. Objectives: We examined the peripheral nervous system involvement, cardiovascular autonomic functions and sympathetic skin responses in Behçet's patients. Methods: Fifteen age and sex matched healthy controls, besides 26 Behçet's patients were included in this study. In order to exclude the effects of colchicine an the parameters tested, 16 patients with familial mediterranean fever (FMF) were also studied. In addition to electromyographic studies and sympathetic skin potentials, variations of R-R interval in electrocardiograhpy in response to hyperventilation and Valsalva manoeuvre were recorded. Patients with disorders that may cause autonomic dysfunction were excluded from the study. Results: There was no difference among the three groups in evaluations performed during hyperventilation and Valsalva manoeuvres. No pathologic electromyographic finding was recorded except the sensory motor polyneuropathy detected in a single Behçet's patient. The amplitude and latencies of skin potentials obtained in Behcet's patients were not significantly different when compared with healthy controls and FMF patients. Colchicine usage did not significantly alter the electrophysiological measurements in Behcet's and FMF patients. Conclusion: There was no evidence of peripheral autonomic nervous system involvement in Behçet's disease. We conclude that autonomic nervous system involvement is not significant in Behçet's disease.